IMPLEMENTASI SECURITY INFORMATION AND EVENT MANAGEMENT (SIEM) DALAM MENINGKATKAN KEAMANAN JARINGAN - Muh. Al Amin; Rakhmadi Rahman (CV. Denasya Smart Publisher, 2024)
In the rapidly evolving digital era, threats to information security have become increasingly complex and diverse. Security Information and Event Management (SIEM) offers a comprehensive solution through the collection, correlation, and analysis of log data from various sources to detect and respond to threats in real-time. This research analyzes the implementation of SIEM in a large organization, highlighting its functionalities, benefits, and challenges, and conducts simulations to test its effectiveness. The results indicate that SIEM can enhance threat detection and response, ensure regulatory compliance, and improve operational efficiency. However, SIEM implementation requires careful planning, competent human resources, and strong management support.